Chemical compatibility between boron oxides and electrolyte and cathode materials of solid oxide fuel cells - Chen, Kongfa; Ai, Na; Jiang, San Ping (Wiley - V C H Verlag GmbH & Co. KGaA, 2013)
Boron is a key component in glass and glass–ceramic sealants for planar solid oxide fuel cells (SOFCs). In this paper, the chemical compatibility between boron and commonly used electrolyte and cathode materials of SOFCs such as Y0.16Zr0.84O2 (YSZ), Gd0.1Ce0.9O2 (GDC), La0.8Sr0.2MnO3 (LSM), La0.6Sr0.4Co0.2Fe0.8O3 (LSCF), SrCo0.2Fe0.8O3 (SCF), and (Ba,Sr)(Co,Fe)O3 (BSCF) are studied. The oxide couples with 43 wt.% H3BO3 (equivalent to 30 wt.% B2O3) were heat-treated at 600–800 °C in air for 20 h. XRD analysis shows that the selected electrolyte and electrode materials are not chemically compatible with boron at temperatures above 600 °C. YSZ and GDC react with boron, forming YBO3 and GdBO3, respectively. In the case of LSM, LSCF, and BSCF powders, the chemical reaction with boron causes the disintegration and decomposition of the perovskite structures. Boron shows a higher reactivity with La2O3 as compared with SrO. On the other hand, the chemical reaction is substantially reduced between volatile boron species and dense electrolyte pellets, but porous electrolyte scaffolds are more susceptible by boron attack as compared to dense electrolyte pellets. The present study suggests that the direct contact between the volatile boron species and electrolyte and cathode materials should be avoided to minimize the detrimental damage of the boron poisoning on the stability and durability of SOFCs.